Epidemiology of Canine Visceral Leishmaniasis in the municipality of Taquarana - AL (2009 - 2018) / Epidemiologia da Leishmaniose Visceral Canina no município de Taquarana - AL (2009-2018) - Jecilãine Efigênia da Silva; Ivan Nascimento de Oliveira; Thaynnara Paula dos Santos Lira; João Pedro Ferreira Barbosa; Ana Marta da Silva Lima; Claudimary Bispo dos Santos (Universidade Estadual de Alagoas, 2019)
Visceral Canine Leishmaniasis (LVC) is a pathology caused by a protozoan of the genus Leishmania, which affects dogs, which are considered, in the urban transmission cycle, the main reservoirs through which humans can become infected. The objective of this work is to show the epidemiological situation of canine visceral leishmaniasis in Taquarana - AL as well as its expansion. The data were collected together with the sanitary surveillance and the endemic area of the city of Taquarana - AL and refer to the period from January 2009 to August 2018. To diagnose canine visceral leishmaniasis, tests such as the DPP and Immunoflorescence. Where 21 cases were registered for dogs with positive serology, during the entire study period, where in the first half of 2018 there were 13 cases. About the resident community in this region was verified that the majority is not aware about the disease. It is possible to observe that sanitary surveillance tries to cure the problems that involve leishmaniasis, however the difficulty of identification by the population does not become feasible, since the lack of knowledge about the disease implies not knowing how to prevent. In this way, it is the responsibility of the municipal health department to promote programs and mobilizations to reduce the occurrence of LVC cases, implementing lectures, promoting health education on prophylactic measures of the disease.